2017
DOI: 10.13075/ijomeh.1896.00823
|View full text |Cite
|
Sign up to set email alerts
|

Impact of road traffic noise on sleep disturbances and attention disorders amongst school children living in Upper Silesian Industrial Zone, Poland

Abstract: Objectives: Published reports suggest that some adverse health impact may be related to noise exposure, and motor vehicle traffic is considered to be the main source of environmental hazard of noise. The aim of this study has been to assess an association between occurrence of sleep and attention disorders with exposure to the noise generated by motor vehicle traffic in the case of a large group of children living in an urban environment. Material and Methods: The data was obtained using a cross sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Road traffic and aircraft noise at school can negatively affect the performance of school-age children, disturbing children’s attention and motivation [ 11 , 12 ], reading comprehension [ 13 , 14 ], short-term memory [ 15 , 16 ], and mathematical skills [ 17 , 18 ]. Associations were found between increased hyperactivity symptomatology in children and both road traffic noise at home [ 19 , 20 ] and traffic and aircraft noise at school [ 21 , 22 ]. In addition, there is some evidence that exposure to long-term traffic noise may increase children’s blood pressure levels [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, First of all, we appreciate the interest of Dr. Kawada [1] that has been aroused by our article that had been published in the "International Journal of Occupational Medicine and Environmental Health" 2017;30(3):511-20 [2]. Authors are aware of limitations of their research, which has been wide ly discussed in the article.…”
Section: On Sleep Disturbances and Attention Disorders Amongst Schoolmentioning
confidence: 99%